Study Protocol for Preventing Early-Onset Pneumonia in Young Children Through Maternal Immunisation: A Multi-Centre Randomised Controlled Trial (PneuMatters) - Chang, Anne B.; Toombs, Maree; Chatfield, Mark D.; Mitchell, Remai; Fong, Siew M.; Binks, Michael J.; Smith-Vaughan, Heidi; Pizzutto, Susan J.; Lust, Karin; Morris, Peter S.; Marchant, Julie M.; Yerkovich, Stephanie T.; et al. (Frontiers in Pediatrics, 2022)
Background: Preventing and/or reducing acute lower respiratory infections (ALRIs) in young children will lead to substantial short and long-term clinical benefits. While immunisation with pneumococcal conjugate vaccines (PCV) reduces paediatric ALRIs, its efficacy for reducing infant ALRIs following maternal immunisation has not been studied. Compared to other PCVs, the 10-valent pneumococcal-Haemophilus influenzae Protein D conjugate vaccine (PHiD-CV) is unique as it includes target antigens from two common lower airway pathogens, pneumococcal capsular polysaccharides and protein D, which is a conserved H. influenzae outer membrane lipoprotein. Aims: The primary aim of this randomised controlled trial (RCT) is to determine whether vaccinating pregnant women with PHiD-CV (compared to controls) reduces ALRIs in their infants’ first year of life. Our secondary aims are to evaluate the impact of maternal PHiD-CV vaccination on different ALRI definitions and, in a subgroup, the infants’ nasopharyngeal carriage of pneumococci and H. influenzae, and their immune responses to pneumococcal vaccine type serotypes and protein D. Methods: We are undertaking a parallel, multicentre, superiority RCT (1:1 allocation) at four sites across two countries (Australia, Malaysia). Healthy pregnant Australian First Nation or Malaysian women aged 17-40 years with singleton pregnancies between 27+6-34+6 weeks gestation are randomly assigned to receive either a single dose of PHiD-CV or usual care. Treatment allocation is concealed. Study outcome assessors are blinded to treatment arms. Our primary outcome is the rate of medically attended ALRIs by 12-months of age. Blood and nasopharyngeal swabs are collected from infants at birth, and at ages 6- and 12-months (in a subset). Our planned sample size (n=292) provides 88% power (includes 10% anticipated loss to follow-up). Discussion: Results from this RCT potentially leads to prevention of early and recurrent ALRIs and thus preservation of lung health during the infant’s vulnerable period when lung growth is maximum. The multicentre nature of our study increases the generalisability of its future findings and is complemented by assessing the microbiological and immunological outcomes in a subset of infants. Clinical Trial Registration: Australia New Zealand Clinical Trial Registry ACTRN12618000150246.